2021
DOI: 10.1093/pubmed/fdab030
|View full text |Cite
|
Sign up to set email alerts
|

Compassion fatigue of funeral directors during and after the first wave of COVID-19

Abstract: Background Compassion fatigue has not been studied among funeral directors. Yet, funeral directors have been exposed to the same risks for compassion fatigue as other caregivers during the coronavirus disease 2019 (COVID-19) pandemic. Methods An online survey was spread two times to 287 employees of funeral home DELA, in Belgium. Once during the height of the first wave of COVID-19 in Belgium, and a second time at the end of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…The aim of the present study was to help expand current research in regard to the context of funeral and mortuary jobs, since they are significantly overlooked especially regarding the study of workplace psychosocial factors that may affect wellbeing [ 1 , 72 ]. To achieve that goal, the JD-R model [ 20 , 21 ] was used as a theoretical framework as it accounts for both the role of job demands and of resources.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of the present study was to help expand current research in regard to the context of funeral and mortuary jobs, since they are significantly overlooked especially regarding the study of workplace psychosocial factors that may affect wellbeing [ 1 , 72 ]. To achieve that goal, the JD-R model [ 20 , 21 ] was used as a theoretical framework as it accounts for both the role of job demands and of resources.…”
Section: Discussionmentioning
confidence: 99%
“…This approach therefore has also practical implications since it can focus not only on job-related risk prevention strategies but also on which significant resources it is possible to invest and promote. Moreover, although the existing research previously identified psychosocial risks in the funeral and mortuary sector [ 5 , 8 , 15 , 16 , 72 ], there is a lack of studies that systematically evaluate both the most relevant job demands and resources and their relationship with the onset of the two core dimensions of burnout, which are emotional exhaustion and cynicism. Among other occupations, a wide array of literature has to date evidenced both health-related and organizational consequences of burnout, e.g., [ 74 , 75 ], that in the funeral context may specifically affect the quality of the service provided and the onset of behaviors that pose a risk to health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This business and product development is included in the scope of microproducts, such as education, Hajj, marriage, health and other service products (Behare and Dharmapurikar, 2013;Gor, 2013). Muslim diasporas in Europe have created similar services by forming Muslim funeral foundations to meet the needs of Muslim diasporas who have died in Europe and wish to be buried in their country of origin due to limited burial grounds and high rents in Europe (Mathijssen and Venhorst, 2019;Corder, 2020;Overmeire et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Since December 2019, the Covid-19 pandemic has claimed more than 5 million lives worldwide (Worldometer, 2022), which has increased the demand for burial land, whose availability is limited. Consequently, the imbalance between demand and supply increases the cost of jenazah handing and funeral service (Chandran and Harrisberg, 2020;Siregar, 2020;Reuters, 2020;Boaheng, 2021;Overmeire et al, 2021;. Gunawan (2015) stated that funeral services in developed countries such as America, Europe and Australia are more expensive.…”
Section: Introductionmentioning
confidence: 99%